«Vengo puro dal puro». Iniziati e non iniziati tra culti misterici, orfismo e rituali per l’aldilà - Cruccas, Emiliano (O T I V M, 2017)
Mystery cults and Orphism represent two important aspects of ancient Greek religion. The connection with concepts like mortality and salvation of the soul is a key point to understand some changes in ancient cults in the transition from Classic to Hellenistic ages. The aim of this paper is to analyse the implications of these changes and the influence of mystery cults in the ancient Greek religion.